Parallel strategy for starter sets to list all permutation based on cycling restriction - Karim, Sharmila; Omar, Zurni; Ibrahim, Haslinda; Othman, Khairil Iskandar (2011)
This paper presents a parallel implementation of a new permutation generation method.This permutation generation method is based on the starter sets for listing all the n! permutations.The sequential algorithm is developed and parallelized for parallel computing by integrating with Message Passing Interface (MPI) libraries. The performance of the parallel algorithms is presented to demonstrate the validation of the works.